Arcivid Chorynia Ruby PENERAPAN MODEL PROBLEM BASED LEARNING MELALUI MEDIA FLEADIO UNTUK MENINGKATKAN KEMAMPUAN MEMBACA DAN MENULIS SISWA TUNANETRA KELAS VI SDLB PURWOSARI : Kata Kunci: Sekolah dasar, Tunanetra, Model Problem Based Learning, Media Flashcard Braille - Wulandari, Sri; Uliyanti, Ilana Anggita; Maharani, Virka Arditya Pramesti; Aisyah, Silviana; Ruby, Arcivid Chorynia (JPI (Jurnal Pendidikan Inklusi), 2021)
Reading and writing are the basic abilities of a learner in the world of education. By reading a student is able to obtain information using word media while writing makes a student able to transform ideas through writing that can be read by others. Apart from normal students, reading and writing are also abilities that must be possessed by inclusive children. This study aims to look for problems in SDLB Purwosari, namely to find out the increase in reading and writing skills through FLEADIO media (flashcard braille animals and audio) in blind children. This study applies a problem-based learning approach, which is a quasi-experimental methodology. Performance evaluations, interviews, and observation are among methods used in data collecting. The analysis of the data was done with basic descriptive statistics. A sixth-grade student at SDLB Purwosari served as the research subject. The study's findings demonstrated that using FLEADIO (braille animals and audio flashcards) media improved the reading and writingabilities of SDLB Purwosari's class VI pupils.